Genesis of the structure of legal relations - I. M. Pohribnyi (Law and Safety)
It is noted that the theory of legal relations appears in the form of a wide and diverse array of knowledge and ideas, of course, it can be accepted as the main source that feeds the very process of further development and improvement of their essence, definition and composition. It is emphasized that two categories of social relations were distinguished in the general theory of law and branch sciences: “organized” and “organizational” social relations. The first always arise to achieve certain goals, the second to normalize the processes “being organized”.